2019
DOI: 10.1016/j.adro.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of Consensus of International Contouring Guidelines for the Dorsal Border of the Chest Wall Clinical Target Volume: What is the Impact on Organs at Risk and Relationships to Patterns of Recurrence in the Modern Era?

Abstract: PurposeVariation exists in cooperative group recommendations for the dorsal border for the chest wall clinical target volume (CTV). We aimed to quantify the impact of this variation on doses to critical organs and examine patterns of chest wall recurrence relative to the pectoralis muscle.Methods and MaterialsWe retrospectively assessed patterns of chest wall recurrence quantified to the recommended CTV borders for women treated between 2005 and 2017. We compared treatment plans for 5 women who were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Considering the limits of the retrospective nature of the included studies and the heterogeneity of the disease stage, treatment and follow-up time, our results are consistent with the results published by Vargo et al, showing that most recurrences were isolated to tissues anterior to the pectoralis muscle. Additionally, Vargo et al reported that up to 23.5% of LRs are located both anterior to and between the pectoralis muscles, while only 11.8% were isolated to the tissue between the pectoralis major and minor (most probably a result of interpectoral nodal recurrence and not 'true' LR) [47,48]. Further studies are needed to analyse the location and timing according to the different types of mastectomy, reconstruction procedures and perioperative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the limits of the retrospective nature of the included studies and the heterogeneity of the disease stage, treatment and follow-up time, our results are consistent with the results published by Vargo et al, showing that most recurrences were isolated to tissues anterior to the pectoralis muscle. Additionally, Vargo et al reported that up to 23.5% of LRs are located both anterior to and between the pectoralis muscles, while only 11.8% were isolated to the tissue between the pectoralis major and minor (most probably a result of interpectoral nodal recurrence and not 'true' LR) [47,48]. Further studies are needed to analyse the location and timing according to the different types of mastectomy, reconstruction procedures and perioperative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Full manuscripts could not be obtained or did not specify the location of recurrences in 74 publications. A total of 14 relevant articles were identified and were included in our meta-analysis [9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…The availability of acellular dermal matrix products has allowed for significant increases in one-stage immediate implant-based reconstruction [31], however concern regarding whether patients may require post-mastectomy chest wall radiation based on final pathological nodal status has led to conservative recommendations [10] 14 (200%) 0 0 14 Farras et al [11] 8 (80%) 2 (20%) 0 10 Gerber et al [12] 4 (66.7%) 0 2 (33.3%) 6 Gilliland et al [13] 50 (80%) 0 10 (20%) 60 Johnson et al [14] 7 (100%) 0 0 7 Meretoja et al [15] 8 (100%) 0 0 8 Noone et al [16] 12 (75.0%) 4 (25.0%) 0 (0%) 16 Pifer et al [17] 11 (64.7%) 6 (35.3%) 0 (0%) 17 Slavin et al [18] 17 (100%) 0 (0%) 0 (0%) 17 Sood et al [19] 6 (100%) 0 0 6 Stanec et al [20] 15 (100%) 0 0 15 Uriburu et al [21] 3 (100%) 0 0 3 Wang et al [22] 96 against immediate reconstruction in patients who may require radiation [32], despite improved cosmetic outcome and quality of life among patients who undergo immediate reconstruction at the time of their mastectomy [33].…”
Section: Discussionmentioning
confidence: 99%
“…dorsal fascia was removed. As indicated above, per ACROP-ESTRO guidelines, in case of absence of tumour invasion into the pectoralis muscle, the pectoral muscle is not part of the CTV (Table 1) [1,7,51].…”
Section: The Common Dissection Planesmentioning
confidence: 99%
“…In any case, the final surgical and histopathological report should indicate if the pectoral dorsal fascia was removed. As indicated above, per ACROP-ESTRO guidelines, in case of absence of tumour invasion into the pectoralis muscle, the pectoral muscle is not part of the CTV ( Table 1 ) [ 1 , 7 , 51 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%